El acceso a sitios web y su incidencia en el desarrollo de las capacidades cognitivas de los jóvenes del 9º y 10º año de educación general básica de la unidad educativa juan Montalvo en el cantón baba provincia los ríos 2016-2017. - Ayala Álava, Luis Eduardo (2016)
Accessibility means that all users, regardless of their disability or their navigation context, can have the services and contents of a website. A website, to be accessible, must contain easily understandable and navigable content; The content must be presented clearly, with simple language and obvious navigation mechanisms to move between pages. Users with disabilities and the elderly may experience a number of problems in accessing web content. It presents the main technical aids that facilitate the processes of interaction and access to content, as well as explore the utilities of browsers used by users with disabilities. In the European Union, web accessibility is quantified and evaluated through the guidelines of the web accessibility initiative. The development of websites and any web-based electronic product that conforms to accessibility guidelines, as well as applicable legislation and regulations, would improve market share and the audience reached by the website by increasing ease of use and Access to the different contents in addition, the implementation of the recommendations would improve the execution of web services and reduce the efforts required for its maintenance. (PABLO LARA NAVARRA Y JOSE ANGEL MARTINEZ, 2006.p7)